Harry Edwards speaking to an audience - Spartan Daily:::Creator::::::::::::
Harry Edwards stands at a podium and is speaking to a student audience in the Morris Daily Auditorium. Behind him are several other faculty and administrators sitting in chairs. This event is focused on addressing civil rights and discrimination issues at San Jose State College.